Distribution of Bemisia tabaci in different agro-ecological regions in Uganda and the threat of vector-borne pandemics into new cassava growing areas - Namuddu, Annet; Seal, Susan; van Brunschot, Sharon; Malka, Osnat; Kabaalu, Richard; Morin, Shai; Omongo, Christopher; Colvin, John (Frontiers in Sustainable Food Systems, 2023)
Previous studies in sub-Saharan Africa have showed the spread of cassava mosaic disease (CMD) and cassava brown streak disease (CBSD) pandemics into different cassava growing regions by high Bemisia tabaci populations. Studies did indicate that there were stark differences in some whitefly species, yet they have not looked extensively across agroecologies. Members of B. tabaci species complex termed sub-Saharan Africa 1 (SSA1) and SSA2 have been linked to the spread of CMD and CBSD viruses. During the period of a severe CMD pandemic in the 1990s, SSA2 was the most predominant until the resurgence of SSA1, particularly SSA1-subgroup1 (SSA1-SG1) from the early 2000s to date. Cassava being a drought resilient crop has become an important food security crop and has been introduced into new areas and regions. Considering the role B. tabaci in the spread of cassava virus pandemics into neighboring regions, we investigated the genetic diversity and distribution of B. tabaci in nine different agro-ecological regions of Uganda in 2017. Adult whiteflies were collected from cassava and 33 other host plants from cassava-growing areas, those with limited cassava and areas with no cassava, where it is being introduced as a food security crop. The partial sequences of the mitochondrial cytochrome oxidase 1 (mtCO1) gene (657 bp) were used to determine the phylogenetic relationships between the sampled B. tabaci. Cassava B. tabaci SSA1 (-SG1, -SG2, -Hoslundia (previously called SSA1-SG1/2), -SG3), SSA2 and SSA3; non-cassava B. tabaci SSA6, SSA10, SSA11, SSA12, SSA13, MED-ASL, MED-Q1, MEAM1, Indian Ocean; and other Bemisia species, Bemisia afer and Bemisia Uganda1 were identified in the study. SSA3, one of the key B. tabaci species that occurs on cassava in West Africa, was identified for the first time in Uganda. The SSA1-SG1 was widely distributed, predominated on cassava and was found on 17 other host-plants. The ability of SSA1-SG1 to exist in environments with limited or no cassava growing poses the risk of continued spread of virus pandemics. Therefore, measures must be put in place to prevent the introduction of diseased materials into new areas, since the vectors exist.